Tinjauan Pustaka: Peran Budaya, Adat dan Tradisi dalam Pola Asuh Sebagai Faktor Penyebab Beban Gizi Ganda Pada Ibu Hamil - Risma Putri Nur Salsabilla; Ridzkiya Karimatus Sholeha2; Septa Indra Puspikawati (Calvaria Medical Journal, 2025)
Background: The double burden of malnutrition among pregnant women remains a critical public health issue in Indonesia. Cultural values, traditions, and patriarchal norms strongly influence caregiving practices, food distribution, and dietary intake within households, thereby shaping maternal nutritional status and contributing to stunting in children. Methods: This study employed a Systematic Literature Review approach by searching Google Scholar and ResearchGate databases using the keywords “Stunting,” “Culture,” “Tradition,” “Customs,” “Parenting,” and “Double Burden of Malnutrition.” Articles were screened according to inclusion and exclusion criteria, resulting in nine eligible studies from an initial 340 and 9 article in analyze. Results: The review revealed that patriarchal culture leads to unequal food distribution and limited decision-making power for women, increasing the risk of micronutrient deficiencies despite excess caloric intake. Food taboos during pregnancy and postpartum further restrict protein and micronutrient consumption. Moreover, early marriage practices and low parental nutrition literacy exacerbate intergenerational malnutrition, where obese mothers coexist with stunted children. On the other hand, evidence highlights the positive role of fathers’ involvement in caregiving and household food decisions, which contributes to improved child nutritional outcomes. Conclusion: The double burden of malnutrition among pregnant women is not merely a biomedical problem but a socio-cultural construct shaped by patriarchal norms, food taboos, and early marriage practices. Addressing this issue requires culturally sensitive nutrition interventions that empower women, promote gender equality, enhance parental nutrition literacy, and strengthen fathers’ roles in childcare and food management to break the cycle of malnutrition across generations.